Faktor-Faktor Kesulitan Menerjemahkan Teks Bahasa Arab - Nurul Hidayah; Muhammad Bachtiar Syamsuddin; Hasmawati Hasmawati (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This research is descriptive quantitative research aimed at getting data about the difficulty of translating the text of the arabic language of 11th grade students of Al Fatih Islamic Senior High School Makassar. The population in this study were all 11th grade students totaling 15 students. The sample used ini the study was a total sample of 15 students. The research data were obtained from interviews, translating tests and questionnaires. The data analysis technique in this study used the percentage technique. Based on the results of the translating test data, it was obatined that in translating Arabic the 11th grade students of Al  Fatih Islamic Senior High School Makassar were classified as very  minimal category with a percentage value of 27.5%. For the results of the study regarding the factor analysis  of students’ difficulties in translating Arabic texts, they are classified into two factors. First, internal factors include the experience of learning Arabic,  students lack of interest in learning Arabic, and low student motivation. Second, external factors, including the student environment, facilities and infrastructure, teachers, and Arabic textbooks.Keywords: Difficulty Factor Analysis, Translating, Arabic text.